THE APPLICATION OF TREASURE HUNTS GAME IN IMPROVING THE STUDENTS’ SPEAKING ABILITY OF SMPN 1 SAKTI - Jamaliah Jamaliah; Fauziah Fauziah; Zaiturrahmi Zaiturrahmi; Masyitah Masyitah (Jurnal Sains Riset, 2022)
The objective of this study was to find out is there any significant different on students’ ability in speaking skill between students’ who are taught by using Treasure Hunts Game and by using conventional method at second year students’ of SMP Negeri 1 Sakti. The sample of this study where class II-3 consist of 22 students and class II-5 consist of 22 students. In this study, the researcher used Treasure Hunts Game as method to teach the students’. The instrument used to collect the data in this research was an oral test. This instrument used both pre-test and post-test, pre-test was given before the researcher treated the students’ by using Treasure Hunts Game, post-test was given after the researcher did an experimental teaching by using Treasure Hunts Game to find out the students’ ability in speaking skill. The data shows that there was a significant different between the students’ who are taught by using the Treasure Hunts Game and the students’ who are taught by using conventional method. The results of pre-test and post-test in experimental class was 76.77 and the result of pre-test and post-test in control class was 65.40. In conclusion there was a significant improve of the students’ speaking ability in the application of Treasure Hunts Game method, Treasure Hunts Game method gives positive effect on students’ speaking ability.Key words: Improving, Speaking Ability, Treasure Hunts Game